Turning cigarette butt waste into an alternative control tool against an insecticide-resistant mosquito vector - Dieng, Hamady; Rajasaygar, Sudha; Abu Hassan, Ahmad; Hamdan, Ahmad; Che Salmah, Md Rawi; Wan Fatma, Zuharah; Satho, Tomomitsu; Miake, Fumio; Fukumitsu, Yuki; Ahmad Ramli Saad, Ramli Saad; Idris, Abd Ghani; Vargas, Ronald Enrique Morales; et al. (Elsevier B.V., 2013)
Annually, 4.5 trillion cigarette butts (CBs) are flicked into our environment. Evidence exists that CB waste is deadly to aquatic life, but their lethality to the aquatic life of the main dengue vector is unknown. CBs are full of toxicants that occur naturally, during planting and manufacturing, which may act as larvicidal agents. We assessed Aedes aegypti vulnerability to Marlboro butts during its development. Overall, CBs showed insecticidal activities against larvae. At early phases of development, mortality rates were much higher in two CBs solution (2CBSol) and 3CBSol microcosms (MICRs). Larval survival gradually decreased with development in 1CBSol-MICRs. However, in great presence of CBs, mortality was high even for the late developmental stages. These results suggest that A. aegypti larvae are vulnerable to CB presence in their habitats, but this effect was seen most during the early developmental phases and in the presence of increased amounts of cigarette remnants. CB filters are being used as raw material in many sectors, i.e., brick, art, fashion, plastic industries, as a practical solution to the pollution problem, the observed butt waste toxicity to mosquito larvae open new avenues for the identification of novel insecticide products.